4CPS-019 Medication use evaluation of edoxaban in a tertiary hospital. (March 2019) - Park, J; You, JH; Lee, SM; Lee, YS; Lee, HK; Kim, JM
Abstract : Background: A new oral anticoagulant (NOAC) edoxaban, which causes less drug-drug or drug-food interactions than warfarin and does not require routine international normalised ratio (INR) monitoring, is associated with a better safety profile in those with renal impairment or low bodyweight, and the elderly. Purpose: To analyse the trend and the appropriateness of edoxaban prescriptions in a tertiary hospital. Material and methods: A retrospective study was conducted using the electronic medical records between April 2016 and August 2017. Patients who initiated treatment with edoxaban between April 2016 and August 2016 were included. We analysed the data to assess if the indications and dosage were appropriate based on the labelling recommendations. We also followed patients' treatment outcomes and adverse events. Results: In total, 142 patients were treated with edoxaban during the observation period. In 94.4% of these patients, edoxaban was prescribed for proper indications, except for eight patients who lacked approved indication for edoxaban use: six were being treated for valvular atrial fibrillation and two for suspected arterial embolism. Among 134 patients with appropriate indications, the percentages of patients whose renal function and bodyweight were measured before initial dosing were 85.8% and 94.0%, respectively. Of the 30 patients who switched from warfarin to edoxaban, 21 patients (70.0%) started edoxaban when the INR ≤2.5. Ninety-three of 134 patients (69.4%) received appropriate an initial dose based on renal function, bodyweight and drug interactions. Thirty patients needed dose modification during administration, but dose adjustments were performed only in eight patients. Twenty patients (14.9%) had adverse drug events, with a total of 30 events, 22 of which were related to bleeding. During the study period, stroke occurred in two patients and no evidence of stroke or pulmonary embolism was observed in 123 patients. Nine patients were lost to follow-up. Conclusion: The majority (≥90%) of patients in our study had indications adequate for edoxaban use, but only 70% of patients received appropriate interventions in terms of dose adjustment and transitioning between anticoagulants. Of the 30 cases of adverse events, 73.3% were bleeding-related events. Therefore, pharmacists need to make more efforts to improve the safe and effective use of edoxaban. References and/or acknowledgements: No conflict of interest.